KAJIAN PENGEMBANGAN KELOMPOK TANI DI KELURAHAN BUHA KECAMATAN MAPANGET KOTA MANADO - Febronia Gledis Manus; Jenny ., Baroleh; Charles R. Ngangi (AGRI-SOSIOEKONOMI, 2018)
This study aims to study the development of "Sukamaju" farmer groups in Buha Village, Mapanget Sub-district, Manado City. This research was conducted from August 2017 to May 2018. The data used are primary and secondary data. Primary data through interviews using questionnaires to 11 respondents and secondary data obtained from the Buha Village Office in Mapanget Sub-district. This analysis uses descriptive analysis. The results of this study indicate that the development of farmer groups in Buha sub-district especially in the "Sukamaju" farmer group development has increased, because with frequent meetings through the development of farmer groups as learning classes, vehicles of cooperation and production units make this farmer group experience excellent development therefore this farmer group belongs to the advanced farmer group.***